(untitled) (Indian Journal of Arid Horticulture, 2025)
Guava is a popular fruit of subtropical area. Guava is one of the recalcitrant plant species for tissue culture. In vitro plant exudation and inborn contamination are two major bottle necks during in vitro culture of guava. Therefore the present study was undertaken to optimize the concentration of phytohormones for micropropagation of guava. Nodal explants were taken for the study and were excised from guava plants maintained in the germplasm block of the institute. Nodal buds (2.5cm length) were excised and brought in the lab in 50mg/1 Ascorbic acid. For surface sterilization Bavestin (200mg/1) was used followed by 0.1% HgCl, for 5 minutes. Explants were inoculated vertically on MS medium supplemented with 50 mg/l PVP and BAP alone or in combination with Kinetin. The cultures were incubated at 25°C in the dark for two days then allowed to grow under a photoperiod of 16/8 hours light and dark period. Among the different combinations of BAP and Kinetin used, MS medium supplemented with 2 ppm BAP, 1 ppm Kinetin and 50 ppm PVP found best for shoot proliferation. MS medium supplemented with 1 ppm IAA found best for rhizogenesis.